The Logistics Cost of Cikarang Dry Port: A General Review - Haryanto, Haryanto; Takrim, Muhammad (JUEB : Jurnal Ekonomi dan Bisnis, 2024)
High logistics costs in Indonesia are thus one of the principal economic inefficiencies that restrain the country's growth and competitiveness in the global marketplace. In this context, the paper focuses on the contribution of the Cikarang Dry Port (CDP) to the national economy. This qualitative research draws on an extended narrative review of the Cikarang Dry Port. These results reflect how the CDP is pivotal in reducing logistics costs, benefiting clients and manufacturing firms around the dry port area through bettered transportation and logistics service provision. The study also puts much emphasis on the fact that logistics efficiency is not only crucial at the level of individual enterprise performance but also, more broadly, for Indonesia's economic landscape. The CDP consolidates supply chains and reduces transportation costs, ultimately building overall cost competitiveness for Indonesian enterprises in more state and international markets. The study calls for the Indonesian government to invest in developing and upgrading the infrastructure of the Cikarang and Bekasi areas. These strategic investments would also help reduce the overall cost of logistics, thereby creating an enabling environment for business operations and playing a role in the economic development and growth of the nation.